Syntthesiis and charactteriizattiion off new macrocyclliic compound ffrom 4-- amiino anttiipyriine - Hashiim M.. Sheerali; Hasan T.. Ghanim (Al-Qadisiyah Journal of Pure Science, 2017)
The target of this work involves synthesis of different new macrocyclic derivatives utilizing two different strategies. The first one involved prepare new azo derivative for (4- amino antipyrine), Through reaction between (4-amino antipyrine) with antipyrine in suitable solvent to form (A1), while the second step involved reaction prepared azo compound with several compounds such as ( urea , thiourea , quanidine , o- phenylene diamine) to form ( A2, A3, A4, A5 ) compounds.